Needs of the Aging LGBT Community in Israel. (July 2019) - Shnoor, Yitschak; Berg-Warman, Ayelet
Since the late 1980s, there have been changes in attitudes toward the LGBT (lesbian, gay, bisexual, and transgender) community in Israel. Nevertheless, the service system for the elderly is largely characterized by heteronormativity and relies on family members to help their elderly relatives.Goal: To examine the difficulties experienced by old LGBT people, particularly in receiving health and social services.Method: A total of 104 LGBT people aged 55+ years responded to a structured online questionnaire.Findings: Compared with the general elderly population, elderly LGBT people have fewer support networks, they tend to live alone, and suffer from tremendous loneliness. They are afraid of coming out to health and social service providers and of functional dependency, particularly due to their fear of disclosing their sexual orientation or gender identity, the barriers to receiving help, and the absence of family support to assist them.